A method for improving high-temperature high-cycle fatigue performance of TiAl alloy through pre-oxidation

CN122918478APending Publication Date: 2026-10-16UNIV OF SCI & TECH BEIJING
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202610974445.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0010]本发明的主要目是为了解决现有技术中提高TiAl合金疲劳性能的方法存在的合金化方法提升性能有限、表面强化处理会在高温服役过程中出现大幅衰减、表面涂层技术的结合力差稳定性弱等技术问题

Benefits of technology

上述方案,本发明提出了一种通过预氧化提高TiAl合金高温高周疲劳性能的方法,能够解决现有技术中提高TiAl合金疲劳性能的方法存在的合金化方法提升性能有限、表面强化处理会在高温服役过程中出现大幅衰减、表面涂层技术的结合力差稳定性弱等技术问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918478A_ABST
    Figure CN122918478A_ABST
Patent Text Reader

Abstract

The application provides a method for improving high-temperature high-cycle fatigue performance of TiAl alloy through pre-oxidation, and relates to the technical field of surface treatment of metal materials and strengthening of fatigue performance. The method comprises the following steps: grinding and polishing a surface of a TiAl alloy workpiece with near lamellar structure to Ra≤0.8 μm; performing pre-oxidation treatment in an oxygen-containing atmosphere or a low-oxygen atmosphere at 750-900 ℃ for 6-24 h; and forming a dense Al2O3-rich oxide layer with a thickness of 0.2-4 μm on the surface after furnace cooling. The application firstly uses pre-oxidation treatment to improve the high-temperature high-cycle fatigue performance of TiAl alloy, and the treated TiAl alloy has a 10 7 The cyclic fatigue limit is improved from 400 MPa to 600 MPa, and the improvement range is 50%. The method has simple process, low cost and good high-temperature service stability, overcomes the performance attenuation of surface treatment methods such as shot blasting at high temperature, and is especially suitable for strengthening the fatigue performance of high-temperature rotating parts such as TiAl alloy turbine blades of an aero-engine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of surface treatment and fatigue performance enhancement of metallic materials, and in particular to a method for improving the high-temperature and high-cycle fatigue performance of TiAl alloys through pre-oxidation. Background Technology

[0002] TiAl intermetallic compound alloys have low densities (3.9-4.2 g / cm³). 3 With its high specific strength, good high-temperature creep resistance, and oxidation resistance, Ti-48Al-2Cr-2Nb (4822 alloy) has partially replaced nickel-based superalloys in the 650-800℃ temperature range for use in high-temperature rotating components such as low-pressure turbine blades in aero-engines and turbochargers in automotive engines. It is a key candidate material for achieving engine lightweighting and improving thrust-to-weight ratio. Among them, Ti-48Al-2Cr-2Nb (4822 alloy) is widely used in the low-pressure turbine blades of several mainstream engines, including GEnx and LEAP.

[0003] However, TiAl alloys face severe environmental degradation during high-temperature service. In high-temperature air environments around 800°C, both non-protective TiO2 and protective Al2O3 are simultaneously formed on the surface of TiAl alloys, creating a complex and poorly dense mixed oxide layer. More critically, oxygen rapidly diffuses inward along the α2 / γ phase interface, preferentially oxidizing the α2 phase lamellar layer, leading to localized embrittlement and microcrack formation. This oxidation-induced damage reduces the fatigue crack initiation life of TiAl alloys in air by about an order of magnitude compared to vacuum conditions. Furthermore, TiAl alloy castings for aero-engines continuously experience temperature and stress changes during service, making them highly susceptible to high-cycle fatigue failure. The existing TiAl alloys have relatively low high-cycle fatigue strength, which is insufficient to meet the high-performance requirements of next-generation high thrust-to-weight ratio advanced aero-engines for lightweight, high-temperature resistant materials.

[0004] Currently, the main methods for improving the fatigue properties of TiAl alloys include the following categories: (1) Alloying method. The strength of TiAl alloy is improved by adding alloying elements such as Nb, Mo, and Si, thereby improving fatigue performance. However, the amount of alloying elements added is limited by the comprehensive mechanical properties such as plasticity and toughness, and the effect of improving fatigue performance is limited.

[0005] (2) Surface strengthening treatment. This includes shot peening, laser shot peening, etc., which delay the initiation of fatigue cracks by introducing residual compressive stress on the surface of the workpiece. For example, Chinese patent CN119795045A discloses "A surface strengthening process to improve the high-cycle fatigue performance of TiAl alloy castings", which uses a combination of sandblasting and shot peening to improve the fatigue strength of the castings; Chinese patent CN119121088A discloses "A method to improve the fatigue performance of TiAl alloys", which uses a combination of hot isostatic pressing, heat treatment and laser shot peening. However, the residual compressive stress introduced by shot peening will be released due to heat exposure during long-term high-temperature service, resulting in a significant decrease in fatigue performance. In addition, Chinese patent CN119571233A discloses a method to improve the high-cycle fatigue performance of Ti6Al4V titanium alloy, which introduces high-amplitude residual compressive stress through shot peening, and then further optimizes the distribution of residual stress and microstructure by combining femtosecond laser shock peening. However, the residual compressive stress introduced by shot peening will be released due to thermal exposure during long-term high-temperature service, leading to a significant decrease in fatigue performance. Although femtosecond laser shock peening can generate ultrafine grains and residual compressive stress fields on the material surface, its equipment is expensive and the process is complex. Furthermore, the compressive stress layer introduced by laser shock is relatively shallow, and stress relaxation problems also exist at high temperatures.

[0006] (3) Thermomechanical treatment method. Mechanical properties of TiAl alloys are improved by controlling the microstructure through hot deformation and heat treatment. For example, Chinese patent CN120249856A discloses a method to improve the mechanical properties of TiAl alloys. By hot deformation treatment (deformation greater than 30%) of β-solidified TiAl alloy ingots, followed by heat treatment in the (α+γ) two-phase region combined with furnace cooling and aging treatment, a near-full lamellar microstructure with spheroidized γ phase is obtained, which improves the room temperature and high temperature plasticity and strength of the alloy. Chinese patent CN111347045A discloses a stepwise hot isostatic pressing preparation method for powder metallurgy titanium alloys. Stepwise hot isostatic pressing is performed at two temperature steps of 850-900℃ and 920-970℃ to break the oxide film on the powder surface to improve the plasticity and high cycle fatigue performance of the alloy. Chinese patents CN116043151A and CN104532060A respectively involve the improvement of fatigue performance of TC4ELI alloy and TC4G improved titanium alloy. However, the aforementioned thermomechanical treatment methods mainly target the overall microstructure optimization of titanium alloys, without addressing the relationship between the active construction of the surface oxide layer and fatigue performance, and their process routes are relatively long and energy-intensive.

[0007] (4) Surface coating technology. This includes protective coatings such as deposited MCrAlY coatings, AlSi coatings, and TiAlCrY coatings. However, problems such as the adhesion between the coating and the substrate, the stability of the coating at high temperatures, and the diffusion of coating elements into the substrate have not yet been fundamentally solved.

[0008] Although current research has explored the use of pre-oxidation to improve the high-temperature oxidation resistance of TiAl alloys. For example, Swad... Ba et al. pre-oxidized γ-TiAl alloys at 900℃ for 2 hours, forming an extremely thin oxide layer of approximately 200-300 nm and an oxygen-rich subsurface layer containing the Z phase (Ti5Al3O2), effectively reducing the oxidation rate of the alloy in the subsequent 300 hours. Chinese patent CN105648398B discloses a method for improving the high-temperature oxidation resistance of TiAl-based alloys through pre-oxidation, which involves providing an environment with extremely low oxygen partial pressure. Chinese patent CN118703930A, entitled "A TiAl alloy with oxidation resistance and its preparation method," discloses a method of high-temperature pre-oxidation treatment at 900-1000℃ for 100-120 minutes in a high-purity oxygen atmosphere, forming a dense Al2O3 oxide layer on the surface of the TiAl alloy to improve its oxidation resistance. In addition, Japanese Patent JPH0641718 discloses a method to improve high-temperature oxidation resistance by forming a thin oxide layer on the surface of heat-resistant materials such as TiAl through pre-oxidation, and then forming a SiO2-based protective film by combining a sol-gel process.

[0009] However, the common limitation of the aforementioned existing technologies is that the purpose and application scope of pre-oxidation treatment are limited to improving the static oxidation resistance of TiAl alloys, while a systematic method for using it to improve high-temperature, high-cycle fatigue performance has not been publicly reported. Given that high-cycle fatigue is one of the main failure modes of high-temperature rotating components such as TiAl alloy turbine blades, insufficient fatigue performance has become a key bottleneck restricting the engineering application of TiAl alloys; therefore, there is an urgent need to develop a fatigue performance improvement method that is simple in process, low in cost, and has good high-temperature service stability. Summary of the Invention

[0010] The main objective of this invention is to address the technical problems existing in current methods for improving the fatigue performance of TiAl alloys, such as limited performance improvement through alloying methods, significant performance degradation during high-temperature service due to surface strengthening treatments, and poor adhesion and stability of surface coatings. Therefore, this invention proposes a method for improving the high-temperature, high-cycle fatigue performance of TiAl alloys through pre-oxidation, which solves the aforementioned problems.

[0011] The technical solution is as follows: A method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys through pre-oxidation, the method comprising the following steps: S1, TiAl alloy material preparation: TiAl alloy materials are prepared using preparation processes including casting, forging, extrusion, and 3D printing; S2. Heat treatment process: The TiAl alloy material of S1 is heat treated to obtain a TiAl alloy workpiece with a near-lamellar structure. S3. Surface pretreatment: The TiAl alloy workpiece with near-lamellar structure in S2 is ground and polished, then cleaned and dried to obtain a smooth and clean TiAl alloy workpiece. S4. Pre-oxidation treatment: Place the smooth and clean TiAl alloy workpiece from S3 into a heat treatment furnace and perform pre-oxidation treatment in an oxygen-containing atmosphere. Then, cool it to room temperature with the furnace to obtain the pre-oxidized TiAl alloy workpiece.

[0012] Optionally, the nominal composition of the TiAl alloy material in S1 includes Ti-44~48Al-2~8Nb-0~2X-0~1Y (at.%), wherein X and Y include Mo, W, Cr, B, and Y; after thermomechanical processing and heat treatment, a near-lamellar structure composed of α2 / γ lamellar clusters, equiaxed γ grains, and a small amount of βo phase is obtained.

[0013] Alternatively, the TiAl alloy material in S1 can be prepared by any of the following methods: Method 1: Casting: The TiAl alloy ingot is melted three times in a vacuum consumable arc furnace and then cast into shape; Method 2: Forging: The TiAl alloy ingot is forged in a multi-directional manner in the β single-phase region or the (α+β) two-phase region, with a forging ratio of not less than 3 and a final forging temperature of not less than 1050℃. Method 3: Extrusion: The TiAl alloy ingot is subjected to two hot extrusions. The first hot extrusion temperature is 1150-1260℃, the extrusion speed is 0.2-0.6m / min, and the extrusion ratio is 4.1-8.1; the second hot extrusion temperature is 1200-1290℃, the extrusion speed is 0.2-0.5m / min, and the extrusion ratio is 3.1-8.1. Method 4, 3D printing: Using selective laser melting or selective electron beam melting additive manufacturing technology, TiAl alloy pre-alloyed powder is used as raw material. It is printed layer by layer under vacuum or inert gas protection, followed by stress-relief annealing and hot isostatic pressing.

[0014] Optionally, the heat treatment in S2 is as follows: the prepared TiAl alloy is heat-treated to obtain a TiAl alloy workpiece with a near-lamellar structure. Specifically, the heat treatment is a two-stage heat treatment: the first stage involves holding at 1200-1260℃ for 10-14 hours and then furnace cooling to room temperature; the second stage involves holding at 1250-1320℃ for 3-15 minutes and then furnace cooling to room temperature.

[0015] Optionally, the TiAl alloy workpiece with near-lamellar structure in S2 obtains a near-lamellar structure composed of α2 / γ lamellar clusters, equiaxed γ grains and a small amount of βo phase, with an average lamellar cluster size of 30-100 μm and an average lamellar spacing of 50-500 nm.

[0016] Optionally, in S3, surface grinding involves mechanically grinding the TiAl alloy workpiece with near-lamellar structure from S1 sequentially with 400#, 800#, 1500#, and 2000# silicon carbide abrasive paper; polishing involves mechanically polishing to a mirror finish with 0.5-2.5μm diamond polishing paste, achieving a surface roughness Ra≤0.8μm; and cleaning involves ultrasonic cleaning in acetone and ethanol for 10-20 minutes each, followed by drying with cold air for later use.

[0017] Optionally, the oxygen-containing atmosphere in S4 is one of dry air, an Ar / O2 mixture, or a vacuum; when using an Ar / O2 mixture, the volume ratio of Ar to O2 is 4:1 to 1:1; the oxygen partial pressure inside the furnace for heat treatment is controlled at 1×10⁻⁶. -2 ~1.01×10 5 Within the Pa range.

[0018] Optionally, the pre-oxidation treatment in S4 is carried out at a temperature of 700-850℃ for 6-24h. The surface of the pre-oxidized TiAl alloy workpiece forms a dense Al2O3-rich oxide layer with a thickness of 0.2-4μm, a density of not less than 95%, a thermal conductivity of 20-35W / (m·K), and a phase composition mainly composed of α-Al2O3.

[0019] Optionally, the pre-oxidized TiAl alloy workpiece in S4 is subjected to a rotating bending fatigue test at 800℃ with a stress ratio R = -1, 10 7 The fatigue limit after one cycle reaches 520-600 MPa, which is 20-50% higher than that of the untreated state.

[0020] Optionally, the room temperature properties of the pre-oxidized TiAl alloy workpieces in S4 are as follows: hardness 350-430, tensile strength 790-880 MPa, yield strength 650-740 MPa, yield ratio 0.80-0.86, elongation 0.8-2.0%, elastic modulus 160-178 GPa, and fracture toughness 17-23 MPa·m. 1 / 2 The high-temperature strength at 650-800℃ is 590-800MPa, the tensile plasticity is 4-14%, and the oxidation weight gain is <0.1mg / (cm³). 2 ·h).

[0021] Technical principle of the invention: This invention breaks through the existing technology's single application mode of pre-oxidation only to improve the static oxidation resistance of TiAl alloys, and for the first time uses it to improve high-temperature, high-cycle fatigue performance. This invention discovers that the fundamental reason for the fatigue performance degradation of TiAl alloys when serving in air at 800℃ is not simply oxidation thinning, but rather oxidation-induced fatigue crack initiation. In a high-temperature air environment, non-protective TiO2 and protective Al2O3 are simultaneously generated on the surface of TiAl alloys, forming a complex and poorly dense mixed oxide layer that cannot effectively block the inward diffusion of oxygen. More importantly, oxygen diffuses rapidly inward along the α2 / γ phase interface, preferentially oxidizing the α2 phase lamellar layer, leading to local embrittlement and microcrack formation, thereby significantly reducing the fatigue crack initiation life.

[0022] Based on the above understanding, this invention proposes to pre-construct a dense Al2O3-rich protective oxide layer on the surface of TiAl alloy workpieces. During subsequent high-temperature fatigue service, this oxide layer exerts a triple protective effect: First, the dense α-Al2O3 oxide layer has an extremely low oxygen diffusion coefficient, effectively blocking the diffusion of external oxygen into the matrix as a physical barrier, inhibiting the preferential oxidation and embrittlement of the α2 phase at the α2 / γ lamellar interface, and avoiding local embrittlement and microcrack formation within the lamellar layers. This is the core mechanism by which this invention improves fatigue performance; Second, the pre-oxidized layer fills the surface roughness... The microscopic defects (scratches, micro-pits, etc.) remaining after grinding and polishing improve the surface density and uniformity, eliminate surface stress concentration sources, and significantly delay the initiation of fatigue cracks on the surface. Thirdly, unlike shot peening, the protective effect of the pre-oxidized layer does not depend on residual compressive stress, but on the excellent thermal stability and chemical inertness of the α-Al2O3 oxide layer itself at 800℃. It remains intact during long-term high-temperature fatigue service and can continuously play a protective role, overcoming the fundamental defect of traditional surface strengthening methods that suffer from performance degradation due to residual stress release caused by high-temperature thermal exposure.

[0023] This invention achieves selective formation of a dense oxide layer with α-Al₂O₃ as the main phase rather than a loose TiO₂ on the surface of TiAl alloys by precisely controlling the temperature and time of the pre-oxidation treatment. The oxide layer thickness is controlled within a reasonable range of 0.2-4 μm; if it is too thin, it cannot effectively prevent oxygen diffusion inward, while if it is too thick, it may cause cracking and spalling during service due to differences in thermal expansion coefficients. The TiAl alloy treated by this invention exhibits a 10-year lifespan at 800℃. 7 The cyclic high-cycle fatigue limit is increased from approximately 400 MPa to 600 MPa, an improvement of 50%, which is at the leading level among the currently disclosed high-cycle fatigue limits of TiAl alloys at 800℃. The method of this invention is simple, requiring only one pre-oxidation treatment in a conventional heat treatment furnace, and is low in cost and easy to promote and apply industrially. It is particularly suitable for strengthening the fatigue performance of high-temperature rotating components such as TiAl alloy turbine blades for aero-engines.

[0024] The above technical solution has at least the following advantages compared with the existing technology: The above-mentioned solution proposes a method to improve the high-temperature and high-cycle fatigue performance of TiAl alloys through pre-oxidation. This method can solve the technical problems of existing methods for improving the fatigue performance of TiAl alloys, such as the limited performance improvement of alloying methods, the significant attenuation of surface strengthening treatment during high-temperature service, and the poor adhesion and weak stability of surface coating technology.

[0025] This invention is the first to use pre-oxidation treatment to improve the high-temperature, high-cycle fatigue performance of TiAl alloys. It breaks through the existing technology's single application of pre-oxidation only to improve oxidation resistance, discovering and utilizing the inhibitory effect of the pre-oxidation layer on the initiation of high-temperature fatigue cracks, thus providing a novel technical path for strengthening the fatigue performance of TiAl alloys.

[0026] The method of this invention significantly improves fatigue performance. Its TiAl alloy exhibits improved fatigue performance at 800℃ for 10... 7 The cyclic high-cycle fatigue limit was increased from approximately 400 MPa to 600 MPa, representing a 50% improvement, which is among the leading levels of the publicly disclosed 800℃ high-cycle fatigue limits for TiAl alloys. In contrast, existing alloying methods generally only improve performance by no more than 5-10%, and shot peening methods suffer from performance degradation after high-temperature heat exposure.

[0027] The method of this invention exhibits excellent high-temperature service stability. The dense Al2O3 oxide layer actively constructed through pre-oxidation remains intact during high-temperature fatigue service, continuously providing oxygen diffusion barrier properties. Unlike the residual compressive stress introduced by shot peening, which is easily released at high temperatures, the protective effect of the pre-oxidation layer does not depend on residual stress, thus demonstrating better high-temperature stability.

[0028] The method of this invention is simple and inexpensive. It requires only one pre-oxidation treatment in a conventional heat treatment furnace, eliminating the need for complex equipment such as shot peening or laser impact, as well as expensive coating deposition systems. Process parameters are easy to control, and it can be directly integrated into existing TiAl alloy component production lines, resulting in extremely low costs for industrial application.

[0029] The method of this invention has a wide range of applications. It is not only applicable to TNM-based TiAl alloys, but can also be extended to other γ-TiAl-based alloys and TiAl-based composite materials for strengthening their high-temperature fatigue properties.

[0030] In summary, compared with existing technologies, the method of this invention utilizes pre-oxidation treatment to pre-construct a dense Al2O3-rich protective oxide layer on the surface of TiAl alloys. This layer acts as an oxygen diffusion barrier during subsequent high-temperature fatigue service, inhibiting the preferential oxidation and embrittlement of α2 lamellars and delaying fatigue crack initiation, thereby significantly improving the high-cycle fatigue limit of TiAl alloys at high temperatures. This method is simple, easy to implement, low in cost, and highly efficient. It avoids the stress release or coating degradation problems caused by high-temperature thermal exposure in existing technologies, making it suitable for large-scale industrial production and widespread application. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0032] Figure 1 This is a surface SEM image of the oxide layer on the surface of TiAl alloy after pre-oxidation treatment, in a method for improving the high-temperature and high-cycle fatigue performance of TiAl alloy by pre-oxidation according to Embodiment 1 of the present invention. Figure 2 This is a cross-sectional SEM image of the oxide layer on the surface of TiAl alloy after pre-oxidation treatment, in a method for improving the high-temperature and high-cycle fatigue performance of TiAl alloy by pre-oxidation according to Embodiment 1 of the present invention. Figure 3 This is a cross-sectional SEM image of the oxide layer on the surface of TiAl alloy after pre-oxidation treatment, in a method for improving the high-temperature and high-cycle fatigue performance of TiAl alloy by pre-oxidation according to Embodiment 2 of the present invention. Figure 4 This is a cross-sectional SEM image of the oxide layer on the surface of TiAl alloy after pre-oxidation treatment, in a method for improving the high-temperature and high-cycle fatigue performance of TiAl alloy by pre-oxidation according to Embodiment 3 of the present invention. Figure 5 This is a cross-sectional SEM image of the oxide layer on the surface of the TiAl alloy after pre-oxidation treatment in Comparative Example 2 of the present invention. Detailed Implementation

[0033] The technical solution of the present invention will now be described with reference to the accompanying drawings.

[0034] In embodiments of the present invention, words such as "exemplarily," "for example," etc., are used to indicate that something is an example, illustration, or description. Any embodiment or design described as "exemplary" in the present invention should not be construed as being more preferred or advantageous than other embodiments or designs. Specifically, the use of the word "exemplary" is intended to present the concept in a concrete manner. Furthermore, in embodiments of the present invention, the meaning expressed by "and / or" can be both, or either one.

[0035] In the embodiments of the present invention, the terms "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction is not emphasized, their intended meanings are consistent.

[0036] In this embodiment of the invention, sometimes a subscript such as W1 may be written in a non-subscript form such as W1. When the difference is not emphasized, the meaning they express is the same.

[0037] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0038] A method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys through pre-oxidation, the method comprising the following steps: S1, TiAl alloy material preparation: TiAl alloy materials are prepared using preparation processes including casting, forging, extrusion, and 3D printing; S2. Heat treatment process: The TiAl alloy material of S1 is heat treated to obtain a TiAl alloy workpiece with a near-lamellar structure. S3. Surface pretreatment: The TiAl alloy workpiece with near-lamellar structure in S2 is ground and polished, then cleaned and dried to obtain a smooth and clean TiAl alloy workpiece. S4. Pre-oxidation treatment: Place the smooth and clean TiAl alloy workpiece from S3 into a heat treatment furnace and perform pre-oxidation treatment in an oxygen-containing atmosphere. Then, cool it to room temperature with the furnace to obtain the pre-oxidized TiAl alloy workpiece.

[0039] Specifically, the nominal composition of the TiAl alloy material in S1 includes Ti-44~48Al-2~8Nb-0~2X-0~1Y (at.%), where X and Y include Mo, W, Cr, B, and Y; after thermomechanical processing and heat treatment, a near-lamellar structure composed of α2 / γ lamellar clusters, equiaxed γ grains, and a small amount of βo phase is obtained.

[0040] Specifically, the TiAl alloy material in S1 is prepared by any of the following methods: Method 1: Casting: The TiAl alloy ingot is melted three times in a vacuum consumable arc furnace and then cast into shape; Method 2: Forging: The TiAl alloy ingot is forged in a multi-directional manner in the β single-phase region or the (α+β) two-phase region, with a forging ratio of not less than 3 and a final forging temperature of not less than 1050℃. Method 3: Extrusion: The TiAl alloy ingot is subjected to two hot extrusions. The first hot extrusion temperature is 1150-1260℃, the extrusion speed is 0.2-0.6m / min, and the extrusion ratio is 4.1-8.1; the second hot extrusion temperature is 1200-1290℃, the extrusion speed is 0.2-0.5m / min, and the extrusion ratio is 3.1-8.1. Method 4, 3D printing: Using selective laser melting or selective electron beam melting additive manufacturing technology, TiAl alloy pre-alloyed powder is used as raw material. It is printed layer by layer under vacuum or inert gas protection, followed by stress-relief annealing and hot isostatic pressing.

[0041] Specifically, the heat treatment in S2 involves heat treating the prepared TiAl alloy to obtain a TiAl alloy workpiece with a near-lamellar structure. Specifically, the heat treatment is a two-stage process: the first stage involves holding at 1200-1260℃ for 10-14 hours followed by furnace cooling to room temperature; the second stage involves holding at 1250-1320℃ for 3-15 minutes followed by furnace cooling to room temperature.

[0042] In particular, the TiAl alloy workpiece with near-lamellar structure in S2 has a near-lamellar structure composed of α2 / γ lamellar clusters, equiaxed γ grains and a small amount of βo phase, with an average lamellar cluster size of 30-100 μm and an average lamellar spacing of 50-500 nm.

[0043] Specifically, in S3, surface grinding involves mechanically grinding the TiAl alloy workpiece with a near-lamellar structure from S1 sequentially with 400#, 800#, 1500#, and 2000# silicon carbide abrasive paper; polishing involves mechanically polishing to a mirror finish with 0.5-2.5μm diamond polishing paste, achieving a surface roughness Ra≤0.8μm; and cleaning involves ultrasonic cleaning in acetone and ethanol for 10-20 minutes each, followed by drying with cold air for later use.

[0044] Specifically, the oxygen-containing atmosphere in S4 is one of dry air, an Ar / O2 mixture, or a vacuum; when using an Ar / O2 mixture, the volume ratio of Ar to O2 is 4:1 to 1:1; the oxygen partial pressure inside the furnace during heat treatment is controlled at 1×10⁻⁶. -2 ~1.01×10 5 Within the Pa range.

[0045] Specifically, the pre-oxidation treatment in S4 is carried out at a temperature of 700-850℃ for 6-24 hours. The surface of the pre-oxidized TiAl alloy workpiece forms a dense Al2O3-rich oxide layer with a thickness of 0.2-4μm, a density of not less than 95%, a thermal conductivity of 20-35W / (m·K), and a phase composition mainly composed of α-Al2O3.

[0046] Specifically, the pre-oxidized TiAl alloy workpiece in S4 underwent a rotating bending fatigue test at 800℃ with a stress ratio R = -1, and 10 7 The fatigue limit after one cycle reaches 520-600 MPa, which is 20-50% higher than that of the untreated state.

[0047] Specifically, the room temperature properties of pre-oxidized TiAl alloy workpieces in S4 are as follows: hardness 350-430, tensile strength 790-880 MPa, yield strength 650-740 MPa, yield ratio 0.80-0.86, elongation 0.8-2.0%, elastic modulus 160-178 GPa, and fracture toughness 17-23 MPa·m. 1 / 2 The high-temperature strength at 650-800℃ is 590-800MPa, the tensile plasticity is 4-14%, and the oxidation weight gain is <0.1mg / (cm³). 2 ·h).

[0048] Example 1

[0049] This embodiment describes a method for improving the high-temperature, high-cycle fatigue performance of a TiAl alloy through pre-oxidation. The TiAl alloy is Ti-44.5Al-4Nb-0.5Mo-0.08B (at.%). The method for improving the high-temperature, high-cycle fatigue performance of the TiAl alloy through pre-oxidation includes the following steps: S1. Preparation of TiAl alloy material: TiAl alloy ingots are subjected to two hot extrusions. The first hot extrusion temperature is 1260℃, the extrusion speed is 30mm / s, and the extrusion ratio is 4.6; the second hot extrusion temperature is 1240℃, the extrusion speed is 30mm / s, and the extrusion ratio is 3.1. Subsequently, a two-stage heat treatment is performed. The first stage involves holding at 1220℃ for 12 hours followed by furnace cooling; the second stage involves holding at 1280℃ for 5 minutes followed by furnace cooling, yielding a TiAl alloy workpiece with a near-lamellar structure. The TiAl alloy workpiece with a near-lamellar structure is rod-shaped, with dimensions of [missing information]. 6×52mm; among which, the near-lamellar structure is composed of α2 / γ lamellar clusters, equiaxed γ grains and a small amount of βo phase, with an average lamellar cluster size of about 50μm and an average lamellar spacing of about 50-500nm; S2. Surface pretreatment: The TiAl alloy workpiece with near-lamellar structure in S1 is subjected to surface grinding, that is, the TiAl alloy workpiece with near-lamellar structure in S1 is mechanically ground with 400#, 800#, 1500# and 2000# silicon carbide sandpaper in sequence; then polished, that is, mechanically polished to a mirror finish with 1μm diamond polishing paste, with a surface roughness Ra=0.8μm; then the polished sample is ultrasonically cleaned in acetone and ethanol for 15min each, and dried with cold air for later use, to obtain a smooth and clean TiAl alloy workpiece. S3. Pre-oxidation treatment: The smooth and clean TiAl alloy workpiece from S2 is placed in a heat treatment furnace (tube furnace) and pre-oxidized in a dry air atmosphere at a temperature of 800℃, a heating rate of 10℃ / min, and a treatment time of 24 hours. Afterward, it is cooled to room temperature in the furnace to obtain the pre-oxidized TiAl alloy workpiece. The surface of the pre-oxidized TiAl alloy workpiece forms the following... Figure 2 The dense Al2O3-rich oxide layer shown is approximately 200-300 nm thick, as... Figure 1 SEM observation of the surface showed that the oxide layer was composed of fine equiaxed oxide particles; the density of the oxide layer was not less than 95%, the thermal conductivity was 30 W / (m·K), and the phase composition was mainly α-Al2O3.

[0050] In this embodiment, the pre-oxidized TiAl alloy workpiece was subjected to a rotary bending fatigue test at a test temperature of 800℃, a stress ratio of R=-1, and a frequency of 80Hz. 7 The high-cycle fatigue limit reaches 600 MPa.

[0051] The room temperature properties of the pre-oxidized TiAl alloy workpiece in this embodiment are as follows: hardness 380, tensile strength 858 MPa, yield strength 723 MPa, yield ratio 0.84, elongation ≥1.52%, elastic modulus 170 GPa, and fracture toughness 22 MPa·m. 1 / 2 The high-temperature strength at 800℃ is 761 MPa, the tensile plasticity is 4.9%, and the weight gain due to oxidation is 0.09 mg / (cm³). 2 ·h).

[0052] Example 2

[0053] This embodiment describes a method for improving the high-temperature, high-cycle fatigue performance of a TiAl alloy through pre-oxidation. The TiAl alloy is Ti-44.5Al-4Nb-0.5Mo-0.08B (at.%). The method for improving the high-temperature, high-cycle fatigue performance of the TiAl alloy through pre-oxidation includes the following steps: S1. Preparation of TiAl alloy material: TiAl alloy ingots are subjected to two hot extrusions. The first hot extrusion temperature is 1260℃, the extrusion speed is 30mm / s, and the extrusion ratio is 4.6; the second hot extrusion temperature is 1240℃, the extrusion speed is 30mm / s, and the extrusion ratio is 3.1. Subsequently, a two-stage heat treatment is performed. The first stage involves holding at 1220℃ for 12 hours followed by furnace cooling; the second stage involves holding at 1280℃ for 5 minutes followed by furnace cooling, yielding a TiAl alloy workpiece with a near-lamellar structure. The TiAl alloy workpiece with a near-lamellar structure is rod-shaped, with dimensions of [missing information]. 6×52mm; among which, the near-lamellar structure is composed of α2 / γ lamellar clusters, equiaxed γ grains and a small amount of βo phase, with an average lamellar cluster size of about 50μm and an average lamellar spacing of about 50-500nm; S2. Surface pretreatment: The TiAl alloy workpiece with near-lamellar structure in S1 is subjected to surface grinding, that is, the TiAl alloy workpiece with near-lamellar structure in S1 is mechanically ground with 400#, 800#, 1500# and 2000# silicon carbide sandpaper in sequence; then polished, that is, mechanically polished to a mirror finish with 1μm diamond polishing paste, with a surface roughness Ra=0.8μm; then the polished sample is ultrasonically cleaned in acetone and ethanol for 15min each, and dried with cold air for later use, to obtain a smooth and clean TiAl alloy workpiece. S3. Pre-oxidation treatment: The smooth and clean TiAl alloy workpiece from S2 is placed in a heat treatment furnace (tube furnace) and pre-oxidized in an Ar / O2 mixed atmosphere (volume ratio Ar:O2=3:1). The treatment temperature is 850℃, the heating rate is 10℃ / min, and the treatment time is 6h. Afterwards, it is cooled to room temperature in the furnace to obtain the pre-oxidized TiAl alloy workpiece. The surface of the pre-oxidized TiAl alloy workpiece forms as shown in the image. Figure 3 The diagram shows a dense Al2O3-rich oxide layer with a thickness of approximately 100-200 nm; the oxide layer has a density of not less than 95%, a thermal conductivity of 25 W / (m·K), and a phase composition dominated by α-Al2O3.

[0054] In this embodiment, the pre-oxidized TiAl alloy workpiece was subjected to a rotary bending fatigue test at a test temperature of 800℃, a stress ratio of R=-1, and a frequency of 80Hz. 7 The high-cycle fatigue limit reaches 580 MPa.

[0055] The room temperature properties of the pre-oxidized TiAl alloy workpiece in this embodiment are as follows: hardness 380, tensile strength 858 MPa, yield strength 723 MPa, yield ratio 0.84, elongation ≥1.52%, elastic modulus 170 GPa, and fracture toughness 22 MPa·m. 1 / 2The high-temperature strength at 800℃ is 761 MPa, the tensile plasticity is 4.9%, and the weight gain due to oxidation is 0.09 mg / (cm³). 2 ·h).

[0056] Example 3

[0057] This embodiment describes a method for improving the high-temperature, high-cycle fatigue performance of a TiAl alloy through pre-oxidation. The TiAl alloy is Ti-44.5Al-4Nb-0.5Mo-0.08B (at.%). The method for improving the high-temperature, high-cycle fatigue performance of the TiAl alloy through pre-oxidation includes the following steps: S1. Preparation of TiAl alloy material: TiAl alloy ingots are subjected to two hot extrusions. The first hot extrusion temperature is 1260℃, the extrusion speed is 30mm / s, and the extrusion ratio is 4.6; the second hot extrusion temperature is 1240℃, the extrusion speed is 30mm / s, and the extrusion ratio is 3.1. Subsequently, a two-stage heat treatment is performed. The first stage involves holding at 1220℃ for 12 hours followed by furnace cooling; the second stage involves holding at 1280℃ for 5 minutes followed by furnace cooling, yielding a TiAl alloy workpiece with a near-lamellar structure. The TiAl alloy workpiece with a near-lamellar structure is rod-shaped, with dimensions of [missing information]. 6×52mm; among which, the near-lamellar structure is composed of α2 / γ lamellar clusters, equiaxed γ grains and a small amount of βo phase, with an average lamellar cluster size of about 50μm and an average lamellar spacing of about 50-500nm; S2. Surface pretreatment: The TiAl alloy workpiece with near-lamellar structure in S1 is subjected to surface grinding, that is, the TiAl alloy workpiece with near-lamellar structure in S1 is mechanically ground with 400#, 800#, 1500# and 2000# silicon carbide sandpaper in sequence; then polished, that is, mechanically polished to a mirror finish with 1μm diamond polishing paste, with a surface roughness Ra=0.8μm; then the polished sample is ultrasonically cleaned in acetone and ethanol for 15min each, and dried with cold air for later use, to obtain a smooth and clean TiAl alloy workpiece. S3. Pre-oxidation treatment: The smooth and clean TiAl alloy workpiece from S2 is placed in a heat treatment furnace, i.e., a box-type resistance furnace, for pre-oxidation treatment under vacuum. The oxygen partial pressure inside the furnace is controlled at 10. -2 The process involves treating a TiAl alloy at 900℃ with a heating rate of 10℃ / min for 24 hours, followed by furnace cooling to room temperature to obtain a pre-oxidized TiAl alloy workpiece. The surface of the pre-oxidized TiAl alloy workpiece forms a surface condition as shown in the image. Figure 4 The diagram shows a dense Al2O3-rich oxide layer with a thickness of approximately 700 nm. The oxide layer has a density of not less than 95%, a thermal conductivity of 30 W / (m·K), and a phase composition dominated by α-Al2O3.

[0058] In this embodiment, the pre-oxidized TiAl alloy workpiece was subjected to a rotary bending fatigue test at a test temperature of 800℃, a stress ratio of R=-1, and a frequency of 80Hz. 7 The high-cycle fatigue limit reaches 520 MPa.

[0059] The room temperature properties of the pre-oxidized TiAl alloy workpiece in this embodiment are as follows: hardness 380, tensile strength 858 MPa, yield strength 723 MPa, yield ratio 0.84, elongation ≥1.52%, elastic modulus 170 GPa, and fracture toughness 22 MPa·m. 1 / 2 The high-temperature strength at 800℃ is 761 MPa, the tensile plasticity is 4.9%, and the weight gain due to oxidation is 0.09 mg / (cm³). 2 ·h).

[0060] Comparative Example 1

[0061] As a comparative example, the Ti-44.5Al-4Nb-0.5Mo-0.08B(at.%) alloy specimens from the same batch were not pre-oxidized, and other conditions were the same as in Example 1. The comparative specimens underwent a rotating bending fatigue test at 800℃ under the same conditions, and their high-cycle fatigue limit of 400MPa was lower than that of the specimens treated by the method of this invention.

[0062] Comparative Example 2

[0063] As a comparative example, Ti-44.5Al-4Nb-0.5Mo-0.08B(at.%) alloy specimens from the same batch were pre-oxidized. After pre-oxidation treatment at 900℃ for 24 hours in air, the oxide film of the TiAl alloy specimens was as follows: Figure 5 As shown, other conditions were the same as in Example 1. The comparative specimen underwent a rotary bending fatigue test at 800°C under the same conditions. Its high-cycle fatigue limit of 290 MPa was lower than that of the specimen treated by the method of this invention, and lower than that of the untreated specimen in Comparative Example 1.

[0064] The above-mentioned solution proposes a method to improve the high-temperature and high-cycle fatigue performance of TiAl alloys through pre-oxidation. This method can solve the technical problems of existing methods for improving the fatigue performance of TiAl alloys, such as the limited performance improvement of alloying methods, the significant attenuation of surface strengthening treatment during high-temperature service, and the poor adhesion and weak stability of surface coating technology.

[0065] This invention is the first to use pre-oxidation treatment to improve the high-temperature, high-cycle fatigue performance of TiAl alloys. It breaks through the existing technology's single application of pre-oxidation only to improve oxidation resistance, discovering and utilizing the inhibitory effect of the pre-oxidation layer on the initiation of high-temperature fatigue cracks, thus providing a novel technical path for strengthening the fatigue performance of TiAl alloys.

[0066] The method of this invention significantly improves fatigue performance. Its TiAl alloy exhibits improved fatigue performance at 800℃ for 10... 7 The cyclic high-cycle fatigue limit was increased from approximately 400 MPa to 600 MPa, representing a 50% improvement, which is among the leading levels of the publicly disclosed 800℃ high-cycle fatigue limits for TiAl alloys. In contrast, existing alloying methods generally only improve performance by no more than 5-10%, and shot peening methods suffer from performance degradation after high-temperature heat exposure.

[0067] The method of this invention exhibits excellent high-temperature service stability. The dense Al2O3 oxide layer actively constructed through pre-oxidation remains intact during high-temperature fatigue service, continuously providing oxygen diffusion barrier properties. Unlike the residual compressive stress introduced by shot peening, which is easily released at high temperatures, the protective effect of the pre-oxidation layer does not depend on residual stress, thus demonstrating better high-temperature stability.

[0068] The method of this invention is simple and inexpensive. It requires only one pre-oxidation treatment in a conventional heat treatment furnace, eliminating the need for complex equipment such as shot peening or laser impact, as well as expensive coating deposition systems. Process parameters are easy to control, and it can be directly integrated into existing TiAl alloy component production lines, resulting in extremely low costs for industrial application.

[0069] The method of this invention has a wide range of applications. It is not only applicable to TNM-based TiAl alloys, but can also be extended to other γ-TiAl-based alloys and TiAl-based composite materials for strengthening their high-temperature fatigue properties.

[0070] In summary, compared with existing technologies, the method of this invention utilizes pre-oxidation treatment to pre-construct a dense Al2O3-rich protective oxide layer on the surface of TiAl alloys. This layer acts as an oxygen diffusion barrier during subsequent high-temperature fatigue service, inhibiting the preferential oxidation and embrittlement of α2 lamellars and delaying fatigue crack initiation, thereby significantly improving the high-cycle fatigue limit of TiAl alloys at high temperatures. This method is simple, easy to implement, low in cost, and highly efficient. It avoids the stress release or coating degradation problems caused by high-temperature thermal exposure in existing technologies, making it suitable for large-scale industrial production and widespread application.

[0071] It should be understood that the term "and / or" in this article is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. Additionally, the character " / " in this article generally indicates an "or" relationship between the preceding and following related objects, but it can also represent an "and / or" relationship. Please refer to the context for a more accurate understanding.

[0072] In this invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of a single item or a plurality of items. For example, at least one of a, b, or c can represent: a, b, c, ab, ac, bc, or abc, where a, b, and c can be a single item or multiple items.

[0073] It should be understood that, in various embodiments of the present invention, the order of the above-mentioned process numbers does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0074] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys through pre-oxidation, characterized in that, The method for improving the high-temperature, high-cycle fatigue performance of TiAl alloys through pre-oxidation includes the following steps: S1, TiAl alloy material preparation: TiAl alloy materials are prepared using preparation processes including casting, forging, extrusion, and 3D printing; S2. Heat treatment process: The TiAl alloy material of S1 is heat treated to obtain a TiAl alloy workpiece with a near-lamellar structure. S3. Surface pretreatment: The TiAl alloy workpiece with near-lamellar structure in S2 is ground and polished, then cleaned and dried to obtain a smooth and clean TiAl alloy workpiece. S4. Pre-oxidation treatment: Place the smooth and clean TiAl alloy workpiece from S3 into a heat treatment furnace and perform pre-oxidation treatment in an oxygen-containing atmosphere. Then, cool it to room temperature with the furnace to obtain the pre-oxidized TiAl alloy workpiece.

2. The method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys by pre-oxidation according to claim 1, characterized in that, The nominal composition of the TiAl alloy material in S1 includes Ti-44~48Al-2~8Nb-0~2X-0~1Y (at.%), where X and Y include Mo, W, Cr, B, and Y. After thermomechanical processing and heat treatment, a near-lamellar structure composed of α2 / γ lamellar clusters, equiaxed γ grains, and a small amount of βo phase is obtained.

3. The method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys by pre-oxidation according to claim 1, characterized in that, The TiAl alloy material in S1 is prepared by any of the following methods: Method 1: Casting: The TiAl alloy ingot is melted three times in a vacuum consumable arc furnace and then cast into shape; Method 2: Forging: The TiAl alloy ingot is forged in a multi-directional manner in the β single-phase region or the (α+β) two-phase region, with a forging ratio of not less than 3 and a final forging temperature of not less than 1050℃. Method 3: Extrusion: The TiAl alloy ingot is subjected to two hot extrusions. The first hot extrusion temperature is 1150-1260℃, the extrusion speed is 0.2-0.6m / min, and the extrusion ratio is 4.1-8.1; the second hot extrusion temperature is 1200-1290℃, the extrusion speed is 0.2-0.5m / min, and the extrusion ratio is 3.1-8.

1. Method 4, 3D printing: Using selective laser melting or selective electron beam melting additive manufacturing technology, TiAl alloy pre-alloyed powder is used as raw material. It is printed layer by layer under vacuum or inert gas protection, followed by stress-relief annealing and hot isostatic pressing.

4. The method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys by pre-oxidation according to claim 1, characterized in that, The heat treatment in S2 is as follows: the prepared TiAl alloy is heat-treated to obtain a TiAl alloy workpiece with a near-lamellar structure; specifically, the heat treatment is a two-stage heat treatment: the first stage is to hold at 1200-1260℃ for 10-14h and then furnace cool to room temperature, and the second stage is to hold at 1250-1320℃ for 3-15min and then furnace cool to room temperature.

5. The method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys by pre-oxidation according to claim 1, characterized in that, In S2, TiAl alloy workpieces with near-lamellar structure obtained a near-lamellar structure composed of α2 / γ lamellar clusters, equiaxed γ grains and a small amount of βo phase, with an average lamellar cluster size of 30-100 μm and an average lamellar spacing of 50-500 nm.

6. The method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys by pre-oxidation according to claim 1, characterized in that, In S3, surface grinding involves mechanically grinding the TiAl alloy workpiece with near-lamellar structure from S1 sequentially with 400#, 800#, 1500#, and 2000# silicon carbide abrasive paper; polishing involves mechanically polishing to a mirror finish with 0.5-2.5μm diamond polishing paste, achieving a surface roughness Ra≤0.8μm; cleaning involves ultrasonic cleaning in acetone and ethanol for 10-20 minutes each, followed by drying with cold air for later use.

7. The method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys by pre-oxidation according to claim 1, characterized in that, The oxygen-containing atmosphere in S4 is one of dry air, an Ar / O2 mixture, or a vacuum; when using an Ar / O2 mixture, the volume ratio of Ar to O2 is 4:1 to 1:1; the oxygen partial pressure inside the furnace during heat treatment is controlled at 1×10⁻⁶. -2 ~1.01×10 5 Within the Pa range.

8. The method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys by pre-oxidation according to claim 1, characterized in that, The pre-oxidation treatment in S4 is carried out at a temperature of 700-850℃ for 6-24 hours. The surface of the pre-oxidized TiAl alloy workpiece forms a dense Al2O3-rich oxide layer with a thickness of 0.2-4μm, a density of not less than 95%, a thermal conductivity of 20-35W / (m·K), and the phase composition is mainly α-Al2O3.

9. The method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys by pre-oxidation according to claim 1, characterized in that, The pre-oxidized TiAl alloy workpiece in S4 was subjected to a rotating bending fatigue test at 800℃ with a stress ratio R=-1. 7 The fatigue limit after one cycle reaches 520-600 MPa, which is 20-50% higher than that of the untreated state.

10. The method for improving the high-temperature, high-cycle fatigue properties of TiAl alloys by pre-oxidation according to claim 1, characterized in that, Room temperature properties of pre-oxidized TiAl alloy workpieces in S4: hardness 350-430, tensile strength 790-880 MPa, yield strength 650-740 MPa, yield ratio 0.80-0.86, elongation 0.8-2.0%, elastic modulus 160-178 GPa, fracture toughness 17-23 MPa·m 1 / 2 The high-temperature strength at 650-800℃ is 590-800MPa, the tensile plasticity is 4-14%, and the oxidation weight gain is <0.1mg / (cm³). 2 ·h).

Citation Information

Patent Citations

  • Ti-6Al-4V improved titanium alloy and processing method thereof

    CN104532060A

  • A method for improving high temperature oxidation resistance of tial-based alloys by pre-oxidation

    CN105648398B

  • Step-by-step hot isostatic pressing preparation method of high-performance powder metallurgy titanium alloy

    CN111347045A

  • Preparation method for prolonging high-cycle fatigue life of TC4ELI alloy

    CN116043151A

  • TiAl alloy with oxidation resistance and preparation method thereof

    CN118703930A